Prospettive nello studio del lessico italiano Atti del IX Congresso SILFI - CRESTI, Emanuela (Proceedings e report, 2008)
The Proceedings of the 9th Conference of the International Society of Italian Linguistics and Philology (SILFI), «Prospects in the study of Italian vocabulary» (Florence, 14-17 June 2006), comprise 88 contributions by scholars from Italy and abroad. The essays are divided into twelve sections, each representing a study prospect, thus illustrating the vitality of the great tradition of Italian studies on language. The Conference confirms the importance of tradition, but also points up how the new areas of study - concerning the use of information infrastructures for the acquisition and conservation of the linguistic heritage - are by now pivotal both for research and for the establishment of essential resources for the defence and promotion of our language. Meditation on the Italian lexicon at this moment in time signifies retrieving the relation between our language and our culture, which tends to be overshadowed in a period of globalisation and of vehicular language such as the present.